Effect of corporate governance and earnings management on expense stickiness - Allolinggi, Theresia Ratte; Saraswati, Erwin; Ghofar, Abdul (International research journal of management, IT and social sciences, 2021)
This study aims to examine and analyze the effect of corporate governance and earnings management on expense stickiness. By defining small positive earnings or small earnings increases as the proxy of earnings management and divides the sample into earnings management (upward earnings management) and non-earnings management. This study uses a broad measure of corporate governance by extracting the main factors of corporate governance. The sample obtained is 251 company samples for earnings management samples and 133 companies for corporate governance samples and processed using the Multiple Linear Regression method using the regression model from the research of Xue and Hong (2016). The results showed that corporate governance can reduce the level of expense stickiness. However, the results of this study cannot prove that earnings management can reduce the level of expense stickiness, but this research proves that companies that do not indicate earning management influence the existence of expense stickiness.